Lenalidomide and Chronic Lymphocytic Leukemia. (19th September 2013) - González-Rodríguez, Ana Pilar; Payer, Angel R.; Acebes-Huerta, Andrea; Huergo-Zapico, Leticia; Villa-Alvarez, Monica; Gonzalez-García, Esther; Gonzalez, Segundo
Abstract : Lenalidomide is an oral immunomodulatory drug used in multiple myeloma and myelodysplastic syndrome and most recently it has shown to be effective in the treatment of various lymphoproliferative disorders such as chronic lymphocytic leukemia (CLL) and non-Hodgkin lymphoma. The mechanism of action of lenalidomide varies depending on the pathology, and in the case of CLL, it appears to primarily act by restoring the damaged mechanisms of tumour immunosurveillance. This review discusses the potential mechanism of action and efficacy of lenalidomide, alone or in combination, in treatment of CLL and its toxic effects such as tumor lysis syndrome (TLS) and tumor flare reaction (TFR), that make its management different from other hematologic malignancies.